Evaluation of the Impact of Metabolic Syndrome on Fibrosis in Metabolic Dysfunction-Associated Fatty Liver Disease - Kani, Haluk Tarik; Demirtas, Coskun Ozer; Keklikkiran, Caglayan; Ergenc, Ilkay; Mehdiyev, Shahin; Akdeniz, Esra; Yilmaz, Yusuf (Turkish Journal of Gastroenterology, 2021)
Background: Metabolic syndrome (MS) is a condition that consists of several disorders, and the individual impact of these disorders on metabolic dysfunction-associated fatty liver disease (MAFLD) is still not clear in a combined diagnosis of MS. In this study, we aimed to investigate the effect of MS on advanced fibrosis in patients with MAFLD. Methods: We recruited the patients from our gastroenterology out-patient clinic who were being followed up for MAFLD. MAFLD was diagnosed with liver biopsy in all patients. The frequency of MS and other metabolic parameters were also compared between groups with advanced fibrosis and groups in which fibrosis was not as advanced. Results: In total, we enrolled 424 biopsy-proven MAFLD patients to the study. In univariate analysis, individuals with greater age, body mass index (BMI), higher aspartate transaminase (AST), MS, impaired fasting glucose, hypertension, enlarged waist circumference (WC), diabetes mellitus (DM), and women had significantly increased risk for fibrosis. In multivariate analysis, it was found that DM, greater age, higher BMI, and increased AST were seen more commonly in MAFLD patients with advanced fibrosis Conclusion: Greater age, a higher BMI, higher AST and a diagnosis of diabetes were more commonly associated with advanced fibrosis. However, DM was found to be the strongest predictive factor of advanced fibrosis in our cohort (OR: 2.495). Multivariate analyses did not indicate a significantly common occurrence of MS in the advanced fibrosis group, despite its important role in MAFLD pathophysiology.